A global assessment of barely visible impact damage for CFRP sub-components with FBG-based sensors. (15th September 2021) - Goossens, Sidney; Berghmans, Francis; Muñoz, Kirsa; Jiménez, Miguel; Karachalios, Evangelos; Saenz-Castillo, Diego; Geernaert, Thomas
Abstract: Barely visible impact damage (BVID) on carbon fibre reinforced polymer (CFRP) aerospace components can create interlaminar defects that may deteriorate during operation with potential failure as a result. Especially damage-prone regions such as the feet of a stiffener must therefore be inspected for BVIDs frequently, which is an effort that increases downtimes and operational costs. The potential of optical fibre sensors as part of a permanently installed structural health monitoring network is well-known. Individual FBG-based strain sensors have shown their capability to detect BVIDs. In this work we introduce a global damage index (GDI) as a figure of merit for the combined response of 60 FBG sensors mounted on several aerospace-grade CFRP flat stiffened panels. We first obtain a detection threshold for the GDI and then demonstrate its use for BVID detection. The proposed methodology is the first of its kind for the representation of the health of a component in a single parameter.